Examining The Impact of The COVID-19 Pandemic On Pediatric Orthopedic Cases: A Systematic Review and Meta-Analysis - Ahmadin Yusuf Rizal Susatyo; Nizar Al Rhaazi; Farhan Haidar Fazlur Rahman; Ismail Hadisoebroto Dilogo (Universitas Airlangga, 2023)
Background: This study examines the adverse effects of COVID-19 pandemic on pediatric orthopedics globally, including decreased patient admissions. The adverse effects of pandemic on pediatric orthopedic patients and surgeries have not been determined. This study aims to conduct a comprehensive systematic review and meta-analysis to investigate the specific impact of COVID-19 pandemic on pediatric orthopedic admissions and surgical cases.Methods: A thorough examination of published literature was performed by searching databases such as PubMed, ScienceDirect, and Cochrane Library, using PRISMA guidelines, and limiting the search to articles published up to January 2022. The primary focus of this review was to inspect the ratio of admission and surgical cases, expressed as a risk ratio (RR) with a 95% confidence level. The study also evaluated any variation among outcomes using the I2 test and examined potential bias using the Egger test. The study findings were calculated using Review Manager 5.4.Results: Fifteen studies were reviewed, revealing a 70% decrease in pediatric orthopedic admissions during the pandemic but no significant difference in admissions between the pandemic and pre-pandemic eras (RR 1.08, 95% CI 0.76-1.54, p=0.66). Furthermore, in the perspective of the pediatric orthopedic surgical case, the pooled analysis also did not show any significant difference between both periods (RR 1.05, 95% CI 0.95 to 1.17, p=0.35). Egger's test result showed no evidence of small-study effects (p = 0.22).Conclusion: This study found that the number of children admitted for orthopedic surgeries and other orthopedic treatments was not greatly impacted during the COVID-19 pandemic.